CgII cleaves DNA using a mechanism distinct from other ATP-dependent restriction endonucleases. Issue 14 (7th July 2017) - Toliusis, Paulius; Zaremba, Mindaugas; Silanskas, Arunas; Szczelkun, Mark D.; Siksnys, Virginijus
Abstract: The restriction endonuclease CglI from Corynebacterium glutamicum recognizes an asymmetric 5′-GCCGC-3′ site and cleaves the DNA 7 and 6/7 nucleotides downstream on the top and bottom DNA strands, respectively, in an NTP-hydrolysis dependent reaction. CglI is composed of two different proteins: an endonuclease (R.CglI) and a DEAD-family helicase-like ATPase (H.CglI). These subunits form a heterotetrameric complex with R2 H2 stoichiometry. However, the R2 H2· CglI complex has only one nuclease active site sufficient to cut one DNA strand suggesting that two complexes are required to introduce a double strand break. Here, we report studies to evaluate the DNA cleavage mechanism of CglI. Using one- and two-site circular DNA substrates we show that CglI does not require two sites on the same DNA for optimal catalytic activity. However, one-site linear DNA is a poor substrate, supporting a mechanism where CglI complexes must communicate along the one-dimensional DNA contour before cleavage is activated. Based on experimental data, we propose that adenosine triphosphate (ATP) hydrolysis by CglI produces translocation on DNA preferentially in a downstream direction from the target, although upstream translocation is also possible. Our results are consistent with a mechanism of CglI action that is distinct from that of other ATP-dependent restriction-modification enzymes.